2009
DOI: 10.3732/ajb.0900041
|View full text |Cite
|
Sign up to set email alerts
|

What's next for science communication? Promising directions and lingering distractions

Abstract: In this essay, we review research from the social sciences on how the public makes sense of and participates in societal decisions about science and technology. We specifically highlight the role of the media and public communication in this process, challenging the still dominant assumption that science literacy is both the problem and the solution to societal conflicts. After reviewing the cases of evolution, climate change, food biotechnology, and nanotechnology, we offer a set of detailed recommendations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
630
0
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 792 publications
(663 citation statements)
references
References 56 publications
9
630
0
24
Order By: Relevance
“…To be effective, science communication must successfully negotiate both channels. That is, in addition to furnishing individuals with valid and pertinent information about how the world works, it must avail itself of the cues necessary to assure individuals that assenting to that information will not estrange them from their communities (Kahan, Slovic, Braman & Gastil 2006;Nisbet & Scheufele 2009;Nisbet 2009). …”
Section: Two Channels Of Science Communicationmentioning
confidence: 99%
“…To be effective, science communication must successfully negotiate both channels. That is, in addition to furnishing individuals with valid and pertinent information about how the world works, it must avail itself of the cues necessary to assure individuals that assenting to that information will not estrange them from their communities (Kahan, Slovic, Braman & Gastil 2006;Nisbet & Scheufele 2009;Nisbet 2009). …”
Section: Two Channels Of Science Communicationmentioning
confidence: 99%
“…Framings communicate how and why the issue should be seen as a problem, how it should be handled, and who is responsible for it Nisbet 2009). Analysing how climate change was framed in the US media and political debate from the late 1990s and onwards, Nisbet and Scheufele (2009) Although underscoring the diversity of climate debates (Hulme 2009), previous studies on media frames of climate change have found the Pandora´s box and conflict frames to be prominent. The former is evident in headlines and coverage articulating fear, misery, and doom (Boykoff 2008), describing climate change as sensational, alarming (Russil and Nyssa 2009) and harmful (Ambler 2007;Carvalho and Burgess 2005).…”
Section: Media Framings Of Climate Changementioning
confidence: 99%
“…More recently, it is increasingly being framed as a political problem. Social scientists, however, have suggested a variety of potential alternative frames, each of which can validly and accurately emphasize other relevant dimensions of the issue-such as public health, national security, extreme weather events, and/or the economy (Nisbet 2009;Nisbet and Scheufele 2009;Maibach et al 2010). Such alternative frames may be more effective at engaging audiences than the environmental or political frames that currently dominate public discourse.…”
mentioning
confidence: 99%
“…Moreover, the way an issue is framed-in the media or in other communications-interacts with audience members' pre-existing schema, mental models and values. As a consequence, a specific message frame is particularly influential to the extent that it is relevant-or applicable-to the audience's preexisting predispositions and perceptions (Nisbet and Scheufele 2009;Scheufele 1999).…”
mentioning
confidence: 99%